Black‐Blood Contrast in Cardiovascular MRI. Issue 1 (19th October 2020) - Henningsson, Markus; Malik, Shaihan; Botnar, Rene; Castellanos, Daniel; Hussain, Tarique; Leiner, Tim
Abstract : MRI is a versatile technique that offers many different options for tissue contrast, including suppressing the blood signal, so‐called black‐blood contrast. This contrast mechanism is extremely useful to visualize the vessel wall with high conspicuity or for characterization of tissue adjacent to the blood pool. In this review we cover the physics of black‐blood contrast and different techniques to achieve blood suppression, from methods intrinsic to the imaging readout to magnetization preparation pulses that can be combined with arbitrary readouts, including flow‐dependent and flow‐independent techniques. We emphasize the technical challenges of black‐blood contrast that can depend on flow and motion conditions, additional contrast weighting mechanisms (T1, T2, etc.), magnetic properties of the tissue, and spatial coverage. Finally, we describe specific implementations of black‐blood contrast for different vascular beds. Level of Evidence: 5 Technical Efficacy Stage: 5